Integrating Religious and Sexual Education in Aceh: A Comprehensive Approach to Prevent Extramarital Sex and Promote Youth Well-being - Tuti Marjan Fuadi; Irdalisa Irdalisa (AL-ISHLAH: Jurnal Pendidikan, 2024)
Sex outside of marriage is prohibited in Muslim society due to religious rules and its potential negative impacts, such as lineage disruption and the spread of sexually transmitted diseases (STDs). In Aceh, adult sexual relations are governed by Islamic law under Qawun Jinayah, which mandates public punishment for offenders. Despite this law being enforced since 2002, extramarital sex and the spread of STDs remain prevalent. This qualitative research uses data from journals and publications in databases like MEDLINE, Scopus, Web of Science, Google Scholar, PubMed, Elsevier, and legal sources. It also reviews textbooks and Qanun Aceh regulations. The study found that prohibitions and preventive measures of Sharia law have not effectively curbed extramarital sexual practices. Young people, especially those under 18, are particularly vulnerable due to inadequate sexual education and insufficient understanding of Islamic law, making them susceptible to sexual violence, STDs, and legal punishments. The research highlights the need for a multifaceted approach to prevention, combining religious, cultural, and comprehensive sexual education for children. Educating youth about religious prohibitions and health risks can reduce their vulnerability and prevent legal repercussions from norm violations. An integrated educational approach in Aceh, which includes collaboration between educators, religious leaders, and policymakers, is crucial. This holistic curriculum would promote healthier and more informed lifestyles among young people, addressing both religious and health education needs.